Aplicativo colaborativo com informações de acessibilidade a serviços e locais turísticos: estudo de caso em Foz do Iguaçu/PR - Rosa, Marcos Roque da (2020)
It is believed that the accessibility is the major challenge for people with disabilities due to architectural obstacles and barriers. Almost all of us, at some point in our lives, may have a disability, temporary or permanent, as a result of an accident or injury, traveling with a family or friend with disabilities. In Foz do Iguaçu, according to IBGE (2010), about 58 thousand people have at least one disability, which may be visual, hearing, physical or motor, mental or intellectual, being that, the same person may have more than one. The city became as a tourist destination, third in the list of ten most visited Brazilian cities for a leisure trip, according to the survey made by Ministry of Tourism in 2018. In this scenario, this research demand to answer the question: How to bring accessibility information for people with disabilities to move more comfortably and safely in the city of Foz do Iguaçu? Therefore, the objective of this work is the development a collaborative application with accessibility information about places of the city of Foz do Iguaçu, in which the following steps were established: scientific research about technologies for people with disabilities, more specifically the application of Geographic Information Systems (GIS); elaboration of accessibility items according to ABNT NBR 9050/2015 standard and the construction of a pilot project for validation the project; and the proposed application development. To go deeper into, a systematic review was made to analyze scientific papers about GIS applied to disabled tourist, that result a theoretical referential and the knowledge construction. Applications that have a large number of users were also analyzed, that help to the elicitation of requirements for development. The accessibility items were listed by the data of accessibility from the Federal University of Latin American Integration (UNILA), and this information used to the pilot project. To develop the application proposed in the research these activities were made: gathering requirements, coding, data loading, testing and digital publishing. As a result, 13 accessibility items were listed and the “Unila Accessible” app was developed. To the final work, the “Accessible Places Map” app was developed, a collaborative guide to accessible tourism for disability.